Effect of Tio2 concentration on photocatalytic degradation of reactive orange 16 Dye (Ro16) - Mezughi, Khaled; Tizaoui, Chedly; Al-Khatib, Ma'an Fahmi Rashid (AENSI Publications, 2014)
Organic contaminants from industrial and/or domestic effluents may be harmful to humans directly or indirectly by degrading the quality of the environment. Consequently these contaminants must be reduced to levels that are not harmful to humans and the environment before disposal. Among the available chemical methods heterogeneous photocatalytic oxidation has been found particularly to be effective in removal of large number of persistent organics in water. Degradation of the organics was achieved by exposing synthetic effluents to UV light in a photocatalytic reactor in a dark compartment in the presence of catalyst. The degradation of RO16 was conducted at pH 5.5, 24 hr, 294 K and lamp power of 200 W. RO16 was prepared in 200 ml dye solution with concentrations of 20, 40 and 60 mg/L and the degradation took place in presence of TiO2 at concentrations of (0.5-4.0) g/L. While photolysis (in absence of TiO2) was found to have no effect on the degradation of RO16, photocatalysis (in presence of TiO2 catalyst) degraded the dye to 0.4 mg/L.